The problems of restoring Ukraine’s own international subjectivity institutedas a result of Russian aggression in the global and regional competition - B. Parahonsky; G. Yavorska (Стратегічна панорама, 2018)
The problems of restoring Ukraine’s own international subjectivity institutedas a result of Russian aggression in the global and regional competition